RADI-18. DIFFUSION KURTOSIS IMAGING CAN HELP DIFFERENTIATE LOW- AND HIGH-GRADE GLIOMAS IN PEDIATRIC PATIENTS: A PROSPECTIVE SINGLE CENTRE STUDY. Issue 2 (22nd June 2018) - Voicu, Ioan Paul; Napolitano, Antonio; Carducci, Chiara; Lattavo, Lorenzo; Espagnet, Maria Camilla Rossi; Carai, Andrea; Cacchione, Antonella; Vinci, Mara; Mastronuzzi, Angela; Tomà, Paolo; Colafati, Giovanna Stefania
Abstract: PURPOSE: To investigate whether diffusion kurtosis imaging (DKI) can be helpful in differentiating low- and high-grade gliomas (LGG and HGG respectively) in pediatric patients. MATERIALS AND METHODS: After obtaining informed consent, thirty-two consecutive children (median age 8.5 years, 17 M) affected by histologically confirmed brain gliomas were prospectively studied on a 3T magnet with a 32-channel head coil. Conventional sequences and DKI sequences (30 directions, 3 b values: 0, 1000, 2000) acquired with the simultaneous multislice (SMS) technique were obtained. Mean kurtosis (MK), axial kurtosis (AK), radial kurtosis (RK) and fractional anisotropy (FA) values were calculated and the corresponding maps were obtained. The enhancing and nonenhancing tumor volumes (VOIs) were segmented semiautomatically. Mean and highest 20 percentile (H20%) DKI values in tumor VOIs were calculated for each metric. Differences among DKI values in the enhancing and nonenhancing VOIs of low and high-grade gliomas (LGG and HGG respectively) were assessed with an independent sample t test. RESULTS: After excluding three patients for motion artifacts, the scans of twenty-nine children (20 LGG and 9 HGG) were analyzed. Significantly different mean RK, H20% RK and mean MK values were found in the enhancing tumor VOI between LGG and HGG (p<0.029, p<0.015 and p<0.05 respectively). CONCLUSIONS: DKI can be helpful in differentiating low and high-grade gliomas in pediatric patients.